Performance on an Interference Task as a Moderator of the Relationship Between COVID-19 Exposure and Posttraumatic Stress Symptoms - Forman, Lily (Tufts Archival Research Center, 2022)
The goal of this study was to determine how the Multi-Source Interference Task (MSIT) might moderate the relationship between COVID-19 exposure and posttraumatic stress symptoms (PTSS). Since the MSIT has previously been shown to be a measure of vulnerability to PTSD, poorer performance on the task may help predict more PTSS after COVID-19 exposure.; Thesis (B.S.)--Tufts University, 2022.; Submitted to the Dept. of Psychology.; Keywords: MSIT performance, COVID-19 exposure, PTSS severity.